A Rare Case of Combined Merkel Cell Cancer and Squamous Cell Carcinoma of the Face in an Older Woman of Southern Italy - Domenico Mariniello, MD; Santolo D’Antonio, MD; Francesco Castellaneta, MD; Michele Grieco, MD, PhD; Tommaso Fabrizio, MD (Plastic and Reconstructive Surgery, Global Open)
Summary:. Merkel cell carcinoma (MCC) is a rare, aggressive neuroendocrine skin tumor, whereas squamous cell carcinoma (SCC) is a more common form of skin cancer. Both tumors share similar risk factors, including advanced age, sun exposure, and fair skin. Cases of synchronous MCC and SCC are rare, and there are no established guidelines for their combined management. We report the case of an 85-year-old White woman from Southern Italy, presenting with a nodular lesion on her right forehead and a flat keratotic lesion on her right zygomatic region. The patient was treated with surgical excision and close postoperative follow-up. Histopathological analysis confirmed 2 distinct tumor populations in the forehead lesion: poorly differentiated neuroendocrine cells, consistent with MCC, and squamous cells with invasive characteristics. The zygomatic lesion contained only squamous cells. Despite surgical intervention and multidisciplinary postoperative care, the patient experienced recurrence within 4 months and died. This case illustrates a rare occurrence of combined MCC and SCC, presenting challenges in diagnosis and treatment. Given the lack of guidelines for managing dual diagnoses, this case highlights the need for further studies to establish standardized treatment protocols. The aggressive nature of these tumors underscores the importance of early detection and ongoing research to improve outcomes.